Marlborough : His Life and Times. - Churchill, Winston S. (Marlborough: His Life and Times., 2014)
The moving conclusion to the acclaimed multivolume biography of one of Britain's greatest military leaders by his even greater descendant. The final installment in Churchill's four-volume biography of John Churchill, the Duke of Marlborough'a famed military leader known for never having lost a military campaign. Despite his successes, Marlborough's later years were full of struggle'including attacks from political and personal enemies. Winston Churchill vividly recounts the intrigues and challenges of his ancestor's extraordinarily eventful life. In this last volume, detailing the end of his career, Marlborough's story is told with sensitivity and nuance'giving the reader an intimate glimpse into his state of mind. It's a fascinating read for anyone interested in English history'and provides profound insights into leadership, loyalty, and personal conduct as valuable today as three centuries ago. "A sustained meditation on statecraft and war by the greatest war leader of our time." 'Foreign Affairs "The greatest historical work written in our century, an inexhaustible mine of political wisdom and understanding, which should be required reading for every student of political science." 'Leo Strauss.